Hubungan Tingkat Stres dengan Sikap pada Generasi Z yang Mengalami Pernikahan Dini di Kecamatan Belawa Kabupaten Wajo - Arni AR; Ruslang Ruslang; Ikdafila Ikdafila; Nirmawati Darwis; Fitriani Fitriani; Uray Wika Suriandani (Journal Research of Nursing & Midwifery (JRNM), 2025)
Generation Z and has implications for psychological conditions, particularly stress, which can influence individuals’ attitudes in navigating married life. This study aims to determine the relationship between stress levels and attitudes among Generation Z individuals who experienced early marriage in Belawa District, Wajo Regency. This study employed a quantitative method with a cross-sectional design. The sample consisted of 30 respondents selected using a total sampling technique. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire to measure stress levels and a Likert scale to assess attitudes. Data analysis was performed using the Chi-Square test with the assistance of SPSS version 22. The results showed a significant relationship between stress levels and attitudes among Generation Z individuals who experienced early marriage, with a p-value of 0.000 (p < 0.05). Generation Z individuals experiencing severe stress tended to exhibit negative attitudes toward married life. It can be concluded that the higher the level of stress, the more negative the attitudes demonstrated.